Recycling perception and practice in Shah Alam municipality - Abdullah Kassim, Nurul Nabila (2017)
The success of solid waste management depends on the participation of household in waste segregation. The attitudes and behavior on recycling should be implemented from home in order for the country to achieve the target of national recycling target. This study was carried out to survey the awareness on the importance of recycling and to make recommendation to improve recycling practice among 100 householders in Shah Alam municipality. All of the respondents will be needed to answer the questionnaire form provided. The respondents were selected from the ‘Zero Waste’ program conducted by Majlis Bandaraya Shah Alam (MBSA). The data was analysed by using Statistical Package for the Social Sciences (SPSS). Analysis show that most of the householders are not practicing recycling at home and are not aware of the consequences of not doing so. This may suggest that there is still a long way to go in educating the society for a sound solid waste management in the country.